A study to assess injection practices at different levels of health care facilities in district Gwalior, M.P., India - Bhargo, Leena; Tiwari, Ranjana; Jain, Swapnil; Yuwane, Praveen; Rajpoot, Maan Bahador; Tiwari, Sakshi (International Journal of Research in Medical Sciences, 2017)
Background: Injections are among the most commonly used medical procedure with an estimated 16 billion administrations each year worldwide. An overwhelming majority (90%-95%) of these injections are administered for curative purposes. Immunization accounts for around 3% of all injections. According to IPEN study, 03-06 billion injections administered annually in India. Estimates suggest that at least 50% of the world’s injections administered each year are unsafe, particularly in developing countries. Most of the curative injections are unnecessary, ineffective or inappropriate. Purpose of current study was to assess and compare the knowledge, skill and practices at different levels of health care by health care providers regarding ‘Safe injection practices’. Methods:The present study has been undertaken in the outdoor departments of government health care facilities of district Gwalior. The study was done at three places namely: Civil dispensaries, district hospital & medical college hospital - Madhav dispensary (Tertiary care hospital) from 1/7/12 - 28/2/13. Results:Only 10 (33.4%) of the providers were aware regarding blood borne injection borne by faulty injection practices, the same number knew about the reasons for wearing the gloves for both patient and personal safety. All the providers had 100% knowledge regarding safe injection practices but in practical many of the skills were lacking at all the health care facilities. Conclusion:There was a great disparity between knowledge and practice of health care provider regarding injection practices. They were quite aware about the transmission of diseases to them by the faulty injection practices but more efforts are needed to be done in this regard for the improvement for the use of safe injection practices in all the health care facilities.